Clinical and Histological Determinants of Mortality for Patients with Barrett’s Esophagus-related T1 Esophageal Adenocarcinoma - Leggett, Cadman L. (Clin Gastroenterol Hepatol, 2014)
BACKGROUND & AIMS: Superficial (T1) esophageal adenocarcinoma (EAC) is commonly treated by endoscopic resection, yet little is known about factors that predict outcomes of this approach. We assessed clinical and histologic variables associated with overall survival times of patients with T1 EAC who received therapy. METHODS: In a retrospective analysis, we collected data from patients who underwent endoscopic mucosal resection (EMR) for T1 EAC (194 with T1a and 75 with T1b) at the Mayo Clinic, from 1995 through 2011. EMR specimens were systematically reviewed for depth of invasion, presence of lymphovascular invasion, grade of differentiation, and status of resection margins. Kaplan-Meier curves and proportional hazards regression models were used in statistical analyses. RESULTS: Demographic characteristics were similar between patients with T1a and T1b EAC. Overall survival at 5 years following EMR was 74.4% for patients with T1a (95% confidence interval [CI], 67.6%−81.8%) and 53.2% for patients with T1b EAC (95% CI 40.3%–70.1%). Of surviving patients with T1a EAC, 94.1% remained free of cancer (95% CI, 89.8%–98.5%), and 94.7% of surviving patients with T1b EAC remained free of cancer (95% CI, 85.2%−100%). A multivariable model associated older age (per 10-year increment), evidence of lymphovascular invasion, and deep margin involvement with reduced overall survival in patients with T1 EAC CONCLUSION: Systematic assessment of EMR specimens can help predict mortality and potentially guide treatment options for patients with T1 EAC.